2009
DOI: 10.3174/ajnr.a1835
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Proton MR Spectroscopy Evaluation of Pyogenic Brain Abscesses: A Report of 194 Cases

Abstract: BACKGROUND AND PURPOSE:The combination of nonspecific clinical findings and similarities in morphologic appearances on imaging often makes it difficult to distinguish abscesses from other brain lesions. We present a retrospective analysis of in vivo 1 H-MR spectroscopy data for characterization of the etiology of the brain abscess based on the established criteria and demonstrate the sensitivity and specificity of metabolite markers assigned to specific bacterial groups defined by the microbial culture in 194 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 27 publications
0
29
1
2
Order By: Relevance
“…alanine in meningiomas, taurine in medulloblastomas) or in pyogenic abscesses as byproducts of fermentation (e.g. succinate and acetate)(1012). …”
Section: Part 1: Mri Of Brain Tumorsmentioning
confidence: 99%
“…alanine in meningiomas, taurine in medulloblastomas) or in pyogenic abscesses as byproducts of fermentation (e.g. succinate and acetate)(1012). …”
Section: Part 1: Mri Of Brain Tumorsmentioning
confidence: 99%
“…Nonvisibility of these resonances in anaerobic culture–positive brain abscesses could be explained by the relatively low concentration of these metabolites, below the sensitivity of the current scanner. 13) Considering a molecular method like polymerase chain reaction as gold standard for the categorization of bacteria in brain abscess, Bajpai et al 14) found a sensitivity and specificity values of in vivo 1H-MRS in culture positive samples of 90% and 100% for aerobic and 87.5% and 90% for anaerobic detection, respectively. …”
Section: Discussionmentioning
confidence: 99%
“…The central necrosis cavity shows absence of normal brain metabolites (choline, creatine, and n-acetyl aspartate). In a series of 194 pyogenic brain abscesses, MR spectroscopy revealed an elevated amino acid level (0.9 ppm) as a marker of proteolytic enzymes from neutrophils in 80% of cases, with a sensitivity of 0.72 and specificity of 0.30 (31).…”
Section: Pyogenic Bacterial Infectionsmentioning
confidence: 98%